Načrtovanje večdimenzionalnih podatkovnih baz - Lahajnar, Sebastian (Uporabna informatika (Ljubljana), 2000)
Today there are many different techniques for data modeling, which are mostly related to relational and object databases. There is also another type of databases in expansive growth, named multidimensional databases, as an important part of OLAP systems. The purpose of the paper is to present all the basic concepts of multidimensional databases, good understanding of which is critical for successful modeling and implementation. The paper also covers basic steps for multidimensional modeling from understanding the current situstion and determing goals, through defining dimensions, hierarchies and members, to the final definition of complex formulas.
Keywords: informacije; informacijski sistemi; modeliranje; objektna tehnologija; OLAP tehnologija; relacijske podatkovne baze